Метрологическое обеспечение исследований наноструктур со сниженным уровнем погрешности преобразования - Слипченко, Н. И.; Федотов, П. Д.; Федотов, Д. А. (ХНУРЭ, 2011)
Analog electronic devices and components performing information signals transformation, as a rule, for computer systems, are urgent when performing metrological investigations into nanostructures. But in this case the parity of a possible precision of the transformation with digital and analog devices is violated. If the digital technique components are renewed every two years perfecting in such a manner the circuit engineering, making it possible to ensure an error nano-level, then the analog devices yield in their development by at least three orders of magnitude. The aim of this work is to substantiate new methods and means for ensuring transformation operations, description of new analog system engineering solutions. Целью данной работы является обоснование новых методов и средств обеспечения операций преобразования, описание новых аналоговых схемотехнических решений.
Keywords: наноэлектроника; метрологическое обеспечение; исследование наноструктур